Veterinary Herd Health Consultancy and Antimicrobial Use in Dairy Herds - Skjølstrup, Nanna K.; Nielsen, Liza R.; Jensen, Carsten S.; Lastein, Dorte B. (Frontiers in Veterinary Science, 2021)
The globally increasing level of antimicrobial resistance affects both human and animal health, and it is therefore necessary to identify ways to change our current use of antimicrobials. Collaboration between veterinarians and dairy farmers provides a useful setting for changing antimicrobial use in livestock. However, farmers and veterinarians work in a complex agricultural setting, which complicates their choices regarding antimicrobial usage. It is therefore necessary to be aware of the range of potential influencing factors and to integrate this knowledge in the relevant local settings. This manuscript presents a literature review of relevant factors relating to antimicrobial use within the veterinary herd health consultancy setting, including knowledge gaps of relevance for changing the use of antimicrobials. We have identified diverging attitudes on correct treatment practices and perceptions of antimicrobial resistance among veterinarians and farmers, influenced by individual risk perception as well as social norms, for example the “pressure to prescribe” experienced by veterinarians, and unwritten social rules connected to being “a good farmer”. Furthermore, disagreements in terms of setting goals and in the frequency of herd visits in relation to herd health consultancy can negatively influence the intention to change antimicrobial use. Farmers and veterinarians emphasise the importance of e.g. legislation and the role of the dairy industry in changing antimicrobial use, but the relevance of specific factors depends on the country-specific context. Overall, farmers and veterinarians must communicate better to understand each other’s perspectives if they are to work efficiently to reduce antimicrobial use. Additionally, there is a need to establish common goals within the collaboration. Farmers and veterinarians both requested changes in individual behaviour based on e.g. improved communication. They also called for national and structural solutions, e.g. balanced legislation and the availability of better diagnostics to facilitate a change in antimicrobial use practices. These various paths to achieving the desired changes in antimicrobial use illustrate the need to bridge methodological research approaches (as discussed in the paper) for a better understanding of our potential to change antimicrobial use within the dairy farm animal sector.